ID 408 – Meralgia paresthetica after the fragmentation of a renal stone using ESWL metod: A case report. Issue 3 (March 2016) - Taşdemir, S.; Cetiz, A.; Yucel, M.; Ulas, U.H.
Abstract : Meralgia paresthetica (MP) is the painful mononeuropathy of the lateral femoral cutaneous nerve (LFCN). LFCN originates from the root of the second and third lumbar nerves and innervates the skin on the anterolateral part of the thigh. MP is presented with burning, pain, numbness, tingling on this part of the thigh. Many different reasons are reported in the etiology. The most common reasons are positional mechanical compression, anterior hip surgery, thigh injury, disc herniation and the use of tight corset or tight belt. We reported a case about MP which occurred with a previously undefined reason in the literature. A 35 -year old- male patient presented with burning and pain on the anterolateral part of the right thigh after the fragmentation of a right renal stone using extracorporeal shock wave lithotripsy. The cortical somatosensory evoked potential (SEP) obtained by innervating of LFCN was longer in the right side than the left side. Lumbar MRI and abdominal computed tomography examination were normal. MP was diagnosed as a result of the clinical findings and the examination of the SEP. Drug was not given to patient due to the absence of severe pain. Symptoms were completely healed after 2 month. SEP was normal bilaterally.